Kedudukan Constitutional Complaint dalam Mahkamah Konstitusional - Putra, Ryan Fachryan Lesmana; Pamungkas, Nandang (Journal of Dual Legal Systems, 2025)
The purpose of this study is to determine the constitutional complaint mechanism based on comparisons in various countries that have been practiced in the Constitutional Court institution. Many cases with constitutional complaint substances have been submitted to the Constitutional Court of the Republic of Indonesia, even though they do not have the authority to do so. This study uses a normative legal research method using a legislative approach, a conceptual approach, a comparative approach, and a case approach. This study shows that the Constitutional Complaint mechanism in Germany, South Korea, and South Africa already exists and has been implemented well. In practice, cases with constitutional complaint substances are submitted to the Constitutional Court of the Republic of Indonesia by changing their form using legal means of testing, such as cases No. 140 / PUU / XIII / 2015 and No. 102 / PUU-VII / 2009. Because it considers the legal structure, substance, and legal culture. Therefore, the adjustment of constitutional complaints within the authority of the Constitutional Court of the Republic of Indonesia needs to be done by amending Law No. 24 of 2003 Jo. Law No. 7 of 2020 concerning the Constitutional Court. [Tujuan dari penelitian ini adalah untuk mengetahui mekanisme constitutional complant berdasarkan perbandingan di berbagai negara yang ditelah dipraktikan dalam lembaga Mahkamah Konstitusi. Banyak kasus dengan substansi constitutional complant yang telah diajukan ke Mahkamah Konstitusi Republik Indonesia, meskipun mereka tidak memiliki kewenangan akan hal tersebut. Penelitian ini menggunakan metode penelitian hukum normatif dengan menggunaan pendekatan perundang-undangan, pendekatan konseptual, pendekatan komparatif, dan pendekatan kasus. Penelitian ini menunjukan bahwa mekanisme Constitutional Complant di Jerman, Korea Selatan, dan Afrika Selatan sudah ada dan telah dilaksanakan dengan baik. Dalam praktiknya, perkara yang substansinya constitutional complaint diajukan ke Mahkamah Konstitusi Republik Indonesia dengan mengubah bentuknya dengan menggunakan sarana hukum pengujian, seperti perkara No. 140/PUU/XIII/2015 dan No. 102/PUU-VII/2009. Karena mempertimbangkan struktur hukum, substansi, dan budaya hukum. Maka penyesuaian konstitusional complaint dalam kewenangan Mahkamah Konstitusi Republik Indonesia perlu dilakukan dengan mengubah UU No. 24 Tahun 2003 Jo. UU No. 7 Tahun 2020 tentang Mahkamah Konstitusi].